Light, mind and spirit: Paul Willis's Learning to Labour revisited on and beyond its 40th anniversary. (December 2018) - Trondman, Mats; Lund, Anna
This article is an introduction to a Special Issue dedicated to Paul Willis's classic Learning to Labour at its 40th anniversary, and beyond. His theoretically informed and theorizing ethnographic study is read, explored, and utilized all around the globe. Its use also stretches across the borders of social, cultural and educational sciences and to manifold research areas and settings. Besides laying out its main content, that is, the answers to the question of how working-class kids let themselves get working-class jobs, this article argues that the most significant contribution of Willis's study is the way it illuminates, both theoretically and empirically, the meaning of cultural production and cultural autonomy in the midst of ongoing social reproduction of class. This introduction ends by presenting the eight contributions to the actual Special Issue, and with an invitation to Paul Willis himself to take issue with cultural production and cultural autonomy.